High Levels of Soluble Endoglin Induce a Proinflammatory and Oxidative-Stress Phenotype Associated with Preserved NO-Dependent Vasodilatation in Aortas from Mice Fed a High-Fat Diet - Jezkova, Katerina; Rathouska, Jana; Nemeckova, Ivana; Fikrova, Petra; Dolezelova, Eva; Varejckova, Michala; Vitverova, Barbora; Tysonova, Kristyna; Serwadczak, Agnieszka; Buczek, Elzbieta; Bernabeu, Carmelo; Lopez-Novoa, Jose M; et al. (Journal of vascular research, 2016)
AIMS: A soluble form of endoglin (sEng) was proposed to participate in the induction of endothelial dysfunction in small blood vessels. Here, we tested the hypothesis that high levels of sEng combined with a high-fat diet induce endothelial dysfunction in an atherosclerosis-prone aorta. METHODS AND RESULTS: Six-month-old female and male transgenic mice overexpressing human sEng (Sol-Eng+) with low (Sol-Eng+low) or high (Sol-Eng+high) levels of plasma sEng were fed a high-fat rodent diet containing 1.25% cholesterol and 40% fat for 3 months. The plasma cholesterol and mouse sEng levels did not differ in the Sol-Eng+high and Sol-Eng+low mice. The expression of proinflammatory (P-selectin, ICAM-1, pNFκB and COX-2) and oxidative-stress-related markers (HO-1, NOX-1 and NOX-2) in the aortas of Sol-Eng+high female mice was significantly higher than in Sol-Eng+low female mice. Endothelium-dependent vasodilatation induced by acetylcholine was preserved better in the Sol-Eng+ high female mice than in the Sol-Eng+low female mice. CONCLUSION: These results suggest that high concentrations of sEng in plasma in combination with a high-fat diet induce the simultaneous activation of proinflammatory, pro-oxidative and vasoprotective mechanisms in mice aorta and the balance of these biological processes determines whether the final endothelial phenotype is adaptive or maladaptive.
Keywords: myši inbrední CBA; Adaptation, Physiological; biologické markery; Mice, Transgenic; mediátory zánětu; aorta; lidé; myši transgenní; vazodilatancia; Atherosclerosis; upregulace; Vasodilator Agents; Inflammation Mediators; Oxidative Stress; fenotyp; Female; Aorta; vztah mezi dávkou a účinkem léčiva; Aortic Diseases; Phenotype; Humans; dieta s vysokým obsahem tuků; fyziologická adaptace; ateroskleróza; Dose-Response Relationship, Drug; oxid dusnatý; Inflammation; Nitric Oxide; endoglin; Disease Models, Animal; Vasodilation; zánět; Biomarkers; Mice, Inbred CBA; mužské pohlaví; vazodilatace; genetická predispozice k nemoci; zvířata; Mice, Inbred C57BL; ženské pohlaví; oxidační stres; Animals; Male; Endoglin; Up-Regulation; modely nemocí na zvířatech; Genetic Predisposition to Disease; Diet, High-Fat; myši inbrední C57BL; nemoci aorty